Crypto Personalities as Carnivalesque Jesters - Serada, Alesha (Emerald, 2024)
In this paper, I discuss the personalities of several representative crypto YouTube celebrities and Bitcoin aficionados, such as George Tung from CryptosRUs, Mike Jenkins (Guy) from Coin Bureau, Lark Davis, Andreas M. Antonopoulos, and Richard Heart. I look closely at their online performances to reveal the character of a trickster, the ambivalent mythological figure that symbolizes chaos, creativity, and disruption. Based on the core literature on the subject, I trace how the figure of a trickster has transformed into the jester in medieval times, and then into the adventurer in the new modern times, and how this transformation is relevant for today. A variety of examples demonstrates that the jester, the trickster, and the adventurer all reveal themselves in different facets of crypto influencers’ performances. However, the most popular YouTubers are also comparatively tame: they produce educational content on cryptocurrencies and blockchain, as compared to “get rich quick” schemes, which are typically presented with a higher degree of tricksteriness. There are also crucial differences and omissions: crypto influencers do not demonstrate queerness, which is inherent to the trickster, and they do not balance praise with abuse, as jesters do. The modern type of an adventurer is more fitting, although it is mostly found in the virtual Wild West of blockchain entrepreneurship, rather than on the most popular YouTube channels.
Keywords: adventurer; celebrity culture; YouTube; trust; tricksters; jesters; fi=Viestintätieteet|en=Communication Studies|